1995
DOI: 10.1055/s-1995-4953
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo- and Enantioselective Synthesis of trans-2-Amino-Cycloalkane-1-Carboxylic Acids via Intramolecular Tandem Michael-Addition/α-Alkylation Using TMS-SAMP as Chiral Equivalent of Ammonia

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Each approach has itsown advantages and limitations while more than 80 numbers of different approaches have been discussed here but the organo-Rh based and heterogeneous catalyzed approach is found to be more effective ( Scheme 1,2,4,11,12,13,28,29) and (Scheme 8,9,33,34,35,36,37,45,54,63). Other approaches can also be considered to synthesize enantioselective amino acids ( Scheme 11,13,15,40,45,50,61,62,68,70,74). No doubt, the growing interest in enantioselective β-amino acids will stimulate new and improved methods for their synthesis in near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each approach has itsown advantages and limitations while more than 80 numbers of different approaches have been discussed here but the organo-Rh based and heterogeneous catalyzed approach is found to be more effective ( Scheme 1,2,4,11,12,13,28,29) and (Scheme 8,9,33,34,35,36,37,45,54,63). Other approaches can also be considered to synthesize enantioselective amino acids ( Scheme 11,13,15,40,45,50,61,62,68,70,74). No doubt, the growing interest in enantioselective β-amino acids will stimulate new and improved methods for their synthesis in near future.…”
Section: Discussionmentioning
confidence: 99%
“…TMS-SAMP as anucleophile was used by Enders et al to synthesis N-silylated β-hydrazino-estersin as aza analogous Michael addition process [67]. In a Tandem aza Michael addition intramolecular cyclization, the same reaction sequence was also applied to the synthesis of cyclic β-amino acids and heterocyclic β-amino acids [68]. Sibi et al reported β-amino acid derivatives with 97% yield (Scheme 45) [69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we designed and synthesized a series of conformationally restricted deltorphin C (Del-C) analogues (Scheme 1) containing cis-and trans-2-or 3-or 4-ACCA at position 2 and evaluated their binding affinity for-µ-, 6-and K-receptors and their resistante to degradation by plasma or brain enzymes. Peptidomimetic 2-or 3-aminocycloalkane-1-carboxylic acid have been designed to replace a single residue in bioactive peptides [18][19][20][21][22] or to prepare oligomers with specific secondary structural preferences (foldamers) [23]. Amino acid derivatives and solid support were purchased from Novabiochem AG (Laufelfingen, Switzerland).…”
Section: Introductionmentioning
confidence: 99%
“…5 The Michael initiated ring closure (MIRC) reaction has been successfully used for the preparation of (1S,2S)-2-aminocycloheptanecarboxylic acid with (S)-(-)-1-(trimethylsilylamino)-2-(methoxymethyl)pyrrolidine (SAMP) as chiral ammonia equivalent. 6,7 The cis-derivatives of the eight-membered b-amino acids have been obtained from cyclooctadiene via its b-lactam 8 or by reduction of 2-acetylamino-1-cyclooctenecarboxylate, 9 but the trans-counterpart has not been successfully synthesized so far.…”
mentioning
confidence: 99%